Kenyamanan Kelompok Binaan Pada Pelaku Ekonomi Kreatif Makanan Berbasis Singkong Melalui Stimulan Dana - Masyhuri Masyhuri (Universitas Negeri Surabaya, 2020)
The purpose of this service is to provide assistance to the cretive economic group based on cassava food. The approach taken in this service is participation in upstream to downstream activities, through mutual agreement from all aspects. The results of the service show that (i) the success of upstream activities, namely cassava farming carried out by the target group has an impact on the 'wheels' of the household economy. This impact is felt because the 'stimulants' of funds based on agreement feel they do not burden them so that in their farming activities there is a 'comfort' guarantee as if there is no risk of returning stimulant funds - there is no traumatic experience in the minds of the perpetrators of farming and / or failure of the 'market'; (ii) the 'comfort' that is developed in the target group is encouraged by the form of stimulant refund in the form of several choices according to 'what' can be done (agreed) by the target group, namely in the form of cassava, cassava, cassava flour, mocaf flour and cassava flour and cassava flour modified with plants that have potential nutritional content of food, such as ˜junggala, ˜kenikir, ˜kemangi, ˜kelor, and others; and (iii) the description of returning 'stimulant funds' is done through a variety of variations, the advantages of this program are the well-built and harmonious comfort, the weakness is that the target group (economic actors) is sometimes unaware of strict responsibilities - even seemingly 'underestimating', constraints - the obstacle that arises is the inaccuracy in returning stimulant funds carried out by the target group, from this the advice that can 'record' is the need for discipline in fulfilling the agreement that is decided. Recommendations that can be submitted to this program are that the program will continue and / or be developed because the social impact is in the form of 'comfort' that appears when / is being / has been running the program. Keywords: comfort, creative economic actors, cassava-based food, fund stimulants